FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTORPERKEBUNAN DAN TANAMAN PANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Latifah Nur Alya (2022)
The purpose of this research is to look at the factors that influence firm value, including profitability as proxied by return on equity (ROE), institutional ownership as proxied by institutional ownership (KI), Corporate Risk Management Disclosures as proxied by enterprise risk management disclosure index. (ERMDI), and debt policy as proxied by debt to equity ratio (DER). The population used in this study are plantation and food crop sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sample used in this study were 8 plantation and food crop subsketing companies from a total population of 22 companies. This study uses panel data regression analysis techniques assisted by the Microsoft Excel 2016 application and the E-Views 10 program, the significance level used is 10%. Where the results of the study show that (1) the profitability variable has no significant effect, (2) institutional ownership has no significant effect, (3) the disclosure of corporate risk management has no significant effect on firm value, while (4) the debt policy variable has a significant effect on firm value.